The Potency of Atorvastatin Nanoparticles Implementation in Human: A Pharmacokinetic Perspective from Basic to Clinical Literature Review - Candra Dwipayana Hamdin; Vania Aisyah Aulia Syahda Haris; Steve Pratama Tanjaya; Shafira Khansa Haiba; Faolananda Qurrota A'yun (Faculty of Medicine, Universitas Mataram, 2026)
Atorvastatin is a biopharmaceutics classification system class II drug with good permeability but low solubility, thereby limiting its bioavailability and therapeutic efficacy. This study aims to analyze the effect of particle size reduction on the pharmacokinetic parameters (Cmax, Tmax, AUC, t½) of atorvastatin in various drug delivery systems and thepotency of its implementation in human through a literature review approach. Literature screening was conducted using online databases including Google Scholar, PubMed, ScienceDirect, and Springer Open, with inclusion criteria of national and international articles published in the last 10 years discussing atorvastatin formulations with various particle sizes and their pharmacokinetic parameters. Analysis of the 11 selected articles showed that nano-based delivery systems can increase the bioavailability of atorvastatin compared to conventional formulations. The results confirmed that particle size reductionthrough nanotechnology approaches increased the dissolution rate, membrane permeability, and absorption efficiency, thereby optimizing the pharmacokinetic profile of atorvastatin. This review provides evidence that nano-scale formulation strategies have a consistent positive impact on the bioavailability of atorvastatin. Despite these promising preclinical findings, the implementation of atorvastatin nanoparticles in humans remains limited due to the absence of clinical trials, although their potency to improve bioavailability and reduce dose-dependent toxicity at lower doses offers a strong rationale for futuretranslational research.